Penerapan Teknologi Mesin Pencacah Sampah Organik Rumah Tangga di Desa Pesucen Kabupaten Banyuwangi - Khairul Muzaka; Ninik Sri Rahayu; Abdul Rohman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Currently, there is a lot of garbage scattered around in the environment, such as the garbage found in small rivers due to the lack of awareness of people who throw garbage in rivers. In fact, throwing garbage in the river causes the overflow of river water so that there is a flood. To overcome these environmental problems, a tool was created, namely the household organic waste chopper, this machine is one solution to reduce waste disposal in the river, which then the results of the enumeration are used for organic fertilizers for plants. Planning for household organic waste choppers as a solution for the environment for the manufacture of organic fertilizer materials as well as to reduce waste that is thrown away, and also the results of the enumeration are used for organic fertilizer on plants. This community service program involves partners and students of the Mechanical Engineering Study Program. The initial stage of this service activity is to conduct a survey to identify the problems faced by partners and conduct a literature study to obtain solutions to partner problems. After the solution to the partner's problem is obtained, the next step is to design and manufacture the machine needed, namely a household organic waste chopper. The household organic waste shredder which is transferred to partners is made as simple as possible, easy to operate and easy to maintain. With the existence of this organic waste shredder, it is hoped that it can help the Pesucen Village community in minimizing piles of organic waste that have a negative impact on the environment